Smart cities: main rankings and improvement proposals for São Luís, Maranhão (Research, Society and Development, 2021)
The concept of smart city (CI) refers to the appropriate place for people to live, with technological resources cooperating with each other, generating well-being, social inclusion and participation of its inhabitants, in addition to the sustainability of the environment, sustainable growth, monitoring and integration of all infrastructure components; preventive maintenance, security, and citizen services. The present study aimed to analyze the main rankings that measure the conditions of cities and classify them among ICs, aiming at improvement proposals for the city of São Luís. For this purpose, it uses the city of Curitiba as a national reference, first place in the Connected Smart Cities Ranking, while São Luís was not among the analyzed positions. It is an applied, qualitative and quantitative, exploratory research, and an intervention plan is proposed to make São Luís more competitive in terms of its classification as a smart and sustainable city, in terms of urban mobility, environment, health, technology and innovation, and security. These items were consolidated in three strategic lines to organize the proposed interventions: Management of public administration; Management of basic sanitation, Adequacy of the use of the territory and the relations between the natural and the built environment, as well as their interferences on mobility in the municipality; in addition to the transversal theme of energy management, combined with the application of sustainable practices and environmental sanitation. Thus, it is possible to transform São Luís into a smart and sustainable city, with investments and partnerships to achieve these goals, improving the quality of life of its inhabitants.